Nanostructured Weight Sensor for A Service Robot Wheel - Pereira Junior, Renato Silva; Quaresma, Luciano; Reis, Marcos Allan; Segundo, Alan; Barros, Luiz; Pessin, Gustavo; Azpúrua, Héctor; Freitas, Gustavo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Intelligent vehicles and autonomous service robots can optimize mobility in complex environments by understanding the interaction between their locomotion systems and the traversed terrain. This paper proposes a sensing method using carbon nanotube-coated sensors applied to a new wheel and tire developed for a service robot, seeking to detect the contact of the locomotion system through the deformation suffered by the interaction with the terrain. The system consists of a trigger pin, a fixing component, and a nanostructured sensor installed in a wheel drum attached to a tire with flexible structure. This article presents the conception, development and implementation of the system’s mechanical and electronic designs, measurement and communication algorithms, and sensor calibration. Preliminary results show the system’s potential to enhance robot traction analysis and motion control in field operations.